Persistence, Time, and Temporal Parts - Lewson, Benjamin J. (Tufts Archival Research Center, 2017)
How can something have two contradictory properties? It can by having them at different times. This paper explores persistence and time, and defends the view that temporal parts are the best way to explain them.